Examination of Football Fans' Levels of Psychological Commitment to The Team, Fanaticism and Happiness - ÇAKMAK, Gökhan; BAŞARAN, Zekiye; KARATUT, Adem (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2022)
Teams try to grow and develop by integrating with their fans. Fans also identify with their teams and are deeply attached to them. In addition, football contains elements that make the spectators and fans happy. The victory of his team will make the spectators and fans happy. The aim of this study is to comparatively examine the psychological commitment to the team, fanaticity and happiness levels of football fans. In this study, descriptive and relational survey model, which is one of the quantitative research methods, was used. The sample of the study consisted of 1285 football fans who were fans of any of the teams competing in the Turkish professional football leagues and participated in the study voluntarily. Personal information questionnaire prepared by the researchers, Team Psychological Commitment Scale, Fanaticism Scale for Football Fans and Oxford Happiness Scale Short Form were used as data collection tools. The data collected within the scope of the research was obtained only through Google Forms due to the pandemic conditions. SPSS 25.0 package program was used in the analysis of the data. Since the data did not comply with the normal distribution characteristics, the Mann-Whitney U test and Kruskal Wallis tests, which are non-parametric tests, were used in the analysis of the data. Multiple comparison tests were used to determine the source of the difference. Spearman Correlation Test was applied to determine the relationship between the scales. As a result, it was determined that 45% of the participants were fans, 29.4% were football fans, and 25.6% were fanatics. It has been determined that those who are fanatics have higher levels of psychological commitment to the team, fanaticity and happiness than those who are male participants than female participants, those who are not members of the support group of their team, those who watch all the matches of their team and those who do not watch. A positive and moderate relationship was found between the levels of fanaticity and psychological commitment levels of the participants. Although the relationship between fanaticity and happiness levels is positive, it is at a low level. It has been determined that there is a low level of positive relationship between psychological commitment levels and happiness levels.